HUBUNGAN KEPATUHAN DIET, AKTIVITAS FISIK DAN TINGKAT STRES DENGAN KADAR GLUKOSA DARAH PADA PENDERITA DIABETES MELITUS TIPE 2 DI PUSKESMAS KUTABUMI KABUPATEN TANGERANG - Edwin Volado (2020)
Diabetes Mellitus is a chronic condition that happened when blood glucose level is increased. It is caused by insulin insufficiency in the blood, or the body cannot use the insulin effectively. Diabetes mellitus is a disease that can't be cured but can be controlled by the patient's blood glucose. The study aims to determine the correlation between dietary compliance, physical activity dan stress level with blood glucose level within patients of diabetes mellitus type 2 in Puskesmas (Community Health Center) Kutabumi Kabupaten Tangerang. The method used in this study is cross sectional with a sample of 40 respondents. This study used primary data from dietary compliance, physical activity, dan stress level questionnaire, while secondary data was blood glucose level from medical records in Puskesmas Kutabumi. The relation analysis was done using the spearman correlation test. The result analysis showed the correlation between dietary compliance (p= 0,000, r= -0.527), physical activity (p= 0,001, r=-0.507), stress level (p= 0.010, r= 0.401) variables with blood glucose level, the reason is because it has <0,05 p-value. Dietary compliance, physical activity dan stress level can affect blood glucose control within type 2 diabetes mellitus patients.